Oczekiwane dochody jako determinanta przedsiębiorczości i ryzyka założenia własnego podmiotu - Tomasz Bernat (Problemy Zarządzania, 2015)
Entrepreneurship takes a central place in the imagination of economists. It is one of the reasons for both growth and development of the economy as well as an individual human being. Determinants and market competences of entrepreneurs indicate the importance of income as a factor supporting the creation of enterprises or deciding on their market survival. Based on this background, the concept of the study was created: do people who want to earn more in the labor market declare entrepreneurship as a method of achieving this aim and do they declare and take the higher risk associated with it. This study was undertaken based on an analysis of survey results and a conducted economic experiment. The results partly answered these research questions.